Visualization of in-cylinder combustion flame and evaluation of engine characteristics of MPFI engine fueled by lemon peel oil blended gasoline. (1st March 2020) - Velavan, A.; Saravanan, C.G.; Vikneswaran, M.; James Gunasekaran, E.; Sasikala, J.
Abstract: This paper reports the results of experimental work carried out on a twin-cylinder gasoline Port Fuel Injection (PFI) engine fueled with lemon peel oil blends. Flame visualization photography is used along with combustion diagnostic tools to investigate the effects of non-octane enhancer bio-fuel lemon peel oil (LPO) on the combustion, performance and emission characteristics of the gasoline engine. The captured combustion flame photographs are post-processed using MATLAB code to single out high diffusion flame regions. The oil extracted from lemon grinds is blended with gasoline in the ratios of 10%, 20% and 30% by volume and tested in the engine at different load conditions. The flame images of 20% and 30% LPO blends show higher diffusion flame regions whereas 10% LPO blend shows least. The gasoline at 80% load shows the least diffusion flames. But the same gasoline shows higher diffusion flame at full load. Among the blends, 10% lemon peel blend shows a better heat release rate compared to gasoline. From the performance analysis, it was determined that the brake thermal efficiency of 10% LPO blend increased by 3% over sole gasoline at full load. The CO, HC, and NOx emission were decreased by 5%, 6.3% and 5% for 10% LPO blend compared to gasoline. From the results, it is concluded that the LPO up to a maximum of 10% by volume can be added with gasoline to improve the performance and emission.